Assessment of Knowledge, Attitudes, and Practice of Community Pharmacists Regarding Weight Reduction Agents and Supplements in Aseer Region, Saudi Arabia - Alshahrani, Sultan M (Risk Manag Healthc Policy, 2020)
PURPOSE: This study investigated the knowledge, attitudes, and practice of community pharmacists regarding weight reduction products in Aseer region, Saudi Arabia. MATERIALS AND METHODS: A questionnaire-based study of community pharmacists in Aseer region, Saudi Arabia, was conducted between March and May 2019. RESULTS: The most commonly prescribed weight reduction agent was green tea followed by oatmeal products and ginseng. The results revealed that almost 85% of the respondents did not know which weight reduction agents are approved as over-the-counter products by the US Food and Drug Administration. Community pharmacists had positive attitudes toward the safety and efficacy of weight reduction products, but 64.91% indicated that they would limit weight reduction agents to obese patients who could not reduce their weight through exercise and diet. More than 80% of the participants agreed that it is very important to counsel patients regarding weight reduction products, and more than 80% also agreed that pharmacists should regularly discuss weight reduction products with other healthcare professionals. CONCLUSION: Community pharmacists showed positive attitudes and efficient practice towards prescribing weight reducing products. However, there was a deficit regarding the knowledge about which products approved by FDA to manage overweight. That requires to consolidate the role of community pharmacists in weight management in Saudi Arabia with more continuous education and regulation.